Biographical Work as a Mechanism of Dealing with Precarity and Precariousness - Burski, Jacek; Mrozowicki, Adam; Drabina-Różewicz, Aleksandra; Krasowska, Agata (Qualitative Sociology Review, 2022)
The article aims to explore the relationship between biographical work and the strategies of managing precarity (low-paid and unstable employment) and precariousness (insecurity and instability of life conditions in general) in Poland’s new capitalism. Poland witnessed the rise of precarity during the entire capitalist transformation after 1989, while the expansion of precarious, temporary, and non-standard employment accelerated in the first two decades of the 21st century. The main theoretical framework of the article is based on concepts deriving from biographical sociology and was elaborated during a joint workshop with German biographical researcher, Fritz Schütze, within the PREWORK project. The case of a young female shop assistant, Helena, with a difficult family and work background was selected from a larger sample of 63 biographical narrative interviews with precarious young workers in Poland. Based on the case study and the broader context of the research project, it is argued that biographical work may have the potential for questioning and challenging precarity; yet, without necessary biographical and social resources, such a process is hard to be completed. As a result, the paper questions the macrosocial vision of “precariat” as the “class in-the-making” and instead offers a detailed account of the microsocial ways of dealing with precarity by a representative of the most disadvantaged group of precarious young workers.